Organizational Culture, Transformational Leadership on Effectiveness of Knowledge Sharing in PMII Organization - Fitrianto, Rizal Idul; Larassaty, Ayu Lucy; Sholikhah, Afifatus; Qurratu’aini, Nafia Ilhama (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research aims to find the influence of organizational culture and the contribution of transformational leadership to knowledge sharing in PMII organization. Methodology: This study adopts a quantitative methodological framework. Data acquisition was carried out via a structured questionnaire, targeting 250 respondents drawn from the population of active PMII members in Sidoarjo, selected through an incidental sampling technique. The analytical procedure encompassed various statistical diagnostics, and determination coefficient analysis were performed utilizing the SPSS. Results:Â The analytical findings reveal that, organizational culture Anda trasformational leadership significant effect on knowledge sharing. Findings: The research concluded that both organizational culture and transformational leadership are pivotal in fostering knowledge sharing. Novelty: The novelty of this study lies in uncovering the mutual role of organizational culture and transformational leadership in strengthening the outcomes of knowledge sharing. Originality: This study lies in its focus which examines the the dynamic between organizational culture and transformational leadership on knowledge sharing. Conclusion:Â This investigation demonstrates that all hypotheses are substantiated, there by offering empirical support for the assertion that both organizational culture and transformational leadership significant influence on knowledge-sharing dynamics within PMII organizations. Type of Paper: Empirical research paper.